Economic evaluation of ion-exchange processes for nutrient removal and recovery from municipal wastewater - Huang, Xiangjun; Guida, Samuela; Jefferson, Bruce; Soares, Ana (Nature Publishing Group, 2020)
Ion exchange (IEX) processes are a promising alternative to remove and recover nutrients from municipal wastewater. To assess the feasibility and viability of IEX processes for full-scale application, this study aimed at providing an evaluation of performance and economics on upscaling these processes for two different configurations in a 10,000 population equivalent wastewater treatment plant (WWTP) and compared them with a traditional biological nutrient removal (BNR) plant. The IEX processes were designed based on existing pilot-scale data, and after aerobic or anaerobic carbon removal stages. The nutrients were recovered from spent regenerants in the form of (NH4)2SO4 and hydroxyapatite Ca5(PO4)3(OH), allowing regenerant reuse. The 40-year whole life cost (WLC) of IEX coupled with traditional activated sludge processes was estimated to be ~£7.4 M, and WLC of IEX coupled with anaerobic membrane process was estimated to be £6.1 M, which was, respectively, 17% and 27% less than the traditional BNR based WWTP. Furthermore, ~98 tonnes of (NH4)2SO4 and 3.4 tonnes of Ca3(PO4)2 could be recovered annually. The benefits of lower costs, reduction in greenhouse gas emissions and nutrient recovery aligned with circular economy, illustrated that IEX processes are attractive for nutrient removal and recovery from municipal wastewater.